The feasibility of a two-day intensive forest therapy incorporating mindfulness practices for natural disaster-affected individuals: a brief report - Lee, Yongjun; Yang, Yeji; Pyo, Ji-Eun; Lee, Beom; Kim, ChangHyou; Choi, Jeong-Ho; Choi, Kee-Hong (Frontiers in Psychology, 2025)
This study investigated the feasibility and psychological benefits of a two-day intensive forest therapy program incorporating mindfulness practices for individuals affected by natural disasters. The sample comprised 110 participants, including those who had either experienced wildfires or floods or served as first responders. The results revealed significant reductions in depression, anxiety, and stress pre- and post-intervention, alongside improvements in vitality and mindfulness. Furthermore, enhanced mindfulness significantly moderated reductions in anxiety, stress, and depression. These findings indicate that intensive forest therapy is a viable and promising intervention for improving the mental health of disaster-affected populations.